The effect of cassava effluent and empty oil palm fruit bunch on remediation of petroleum polluted soil and crop production in the tropics: A review - Fidelis Ifeakachuku Achuba; Oke Aruoren; Abigail Chioma Nmanedu; Patrick Chukwuyenum Ichipi-Ifukor; Uche Dennis-Eboh (International Journal of Recycling of Organic Waste in Agriculture)
Purpose There is an increased demand for proper utilization of wastes to benefit humans especially as it relates to generation of economic gains. Although the agro-based industry and the petroleum industry contribute to high levels of waste generation, it is possible that the wastes from the agro industry could be used for management of petroleum hazards and pollution. This review focuses on the identification of potential benefits of two highly ignored agro wastes: cassava effluent and empty oil palm bunch, which contribute to the emission of greenhouse gases and increasing the disease causing potentials of these wastes for people living where they are disposed. Methods In this review, we utilized available literature to reveal the importance of agro wastes as well as their different beneficial applications especially as they concern the remediation of crude oil pollution. Results Evidence from previous research indicates that cassava effluent contains some beneficial nutrient components that negatively affect soil chemistry and plant growth. The use of empty oil palm bunch, on the other hand, has been reported to contribute to the improvement of soil nutrient properties and crop production. Conclusion We postulate that the chemical constituent of these two agricultural wastes may significantly complement their ability to improve crop production when combined, as well as mediate cleanup of soils exposed to crude oil pollution over time.